Strengthening the Competency of Pakal District Kindergarten Teachers Through the Creation and Implementation of Illustration-Based Educational Game Tools (APE) in Introducing the Spirit of National Defense - Handayani, Wiwik; Dewanti, Mentari Clara; Romadhona, Mahimma; Mandasari, Virginia (Nusantara Science and Technology Proceedings, 2023)
A creative and innovative learning process is an effort to produce creative students, through student activities when studying and the creativity that students can carry out after learning. The key to success in creative and innovative learning lies in the role of the teacher, where teachers are able to create effective learning and facilitate students in developing logical thinking skills. Based on the results of observations carried out in kindergartens in Pakal District, Surabaya City, it shows that the learning process carried out by teachers still lacks creative and innovative teaching and learning activities for students. So far, teachers are only limited to giving lectures and there is a lack of teaching aids in delivering the material, making students less interested in learning. One of the teaching aids that can be used in the learning process is to use illustration-based educational games (APE). The role of teachers at the kindergarten education level can be to select and develop creative and innovative learning resources through educational game tools which can be designed and made as game tools to improve student development. This activity is expected to produce teachers who are able to create illustration-based educational game tools (APE). It is hoped that illustration-based educational teaching aids (APE) will create a creative and innovative learning process for students in partners, as well as provide a social impact on the surrounding community in creating effective learning for children.